Already dead - Eberts, Christopher; Jam, Kia, 1970-; Griffen, Colleen; Chappelle, Joe.; Lynn, Robert, 1918-1982.; Alford, David; Otting, Joe, 1974-; Eldard, Ron, 1964-; Schweiger, Til, 1963-; Kilpatrick, Patrick; Pierson, Geoff; Coughlan, Marisa, 1974-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2008)
Thomas Archer had everything: a beautiful wife, a job as a senior associate at a powerful architecture firm, and a beautiful son. Until one fateful night, when his son was taken from him and his wife brutalized, sending Archer down a path of revenge.
Title from container.
Director of photography, Eric Trageser ; editor, Adam Sobocienski ; music, Nathan Furst ; production designer, Ermanno Di Febo-Orsini.
Ron Eldard, Til Schweiger, Patrick Kilpatrick, Geoff Pierson, Marisa Coughlan, Christopher Plummer.
MPAA rating: R; for violence and language.
DVD, region 1, anamorphic widescreen (2.35:1) presentation; Dolby Digital 5.1, DTS.
English, Thai, Spanish, or French dialogue with optional English, Korean, Thai, Spanish, Chinese, or French subtitles; closed-captioned.
Keywords: Murder -- Drama; Man-woman relationships -- Drama; Revenge -- Drama; Thrillers (Television programs); Thrillers (Motion pictures); Feature films; Thrillers (Motion pictures)